1995
DOI: 10.1097/00003246-199503000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying in critically ill patients is accelerated by adding cisapride to a standard enteral feeding protocol

Abstract: The data indicate that gastric emptying in critically ill, sedated, and mechanically ventilated patients can be significantly improved by adding cisapride to a routine enteral feeding protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(43 citation statements)
references
References 21 publications
0
42
0
1
Order By: Relevance
“…In ICU settings, metoclopramide, cisapride, and erythromycin have been used to facilitate tube progression beyond the pylorus, although with variable success. Metoclopramide has unpredictable effects while cisapride, an excellent prokinetic agent [16,17], has un- wanted deleterious cardiac side effects in critically ill related to its ability to increase the QT interval on ECG [18]. It has been shown in healthy volunteers that 40 mg of erythromycin induces premature antral activity, which migrates through the small intestine, while 200 mg causes a prolonged period of enhanced antral activity due to direct muscular receptor activation [19].…”
Section: Discussionmentioning
confidence: 99%
“…In ICU settings, metoclopramide, cisapride, and erythromycin have been used to facilitate tube progression beyond the pylorus, although with variable success. Metoclopramide has unpredictable effects while cisapride, an excellent prokinetic agent [16,17], has un- wanted deleterious cardiac side effects in critically ill related to its ability to increase the QT interval on ECG [18]. It has been shown in healthy volunteers that 40 mg of erythromycin induces premature antral activity, which migrates through the small intestine, while 200 mg causes a prolonged period of enhanced antral activity due to direct muscular receptor activation [19].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of administration was 100±150 ml/h, with a standard rinse of 50 ml (25±100 ml) water adjusted to the daily requirement assessed by daily intake and output. Residual volume was measured before each feeding; feeding was delayed by 4 h if this was more than 300 ml, and cisapride (10 mg every 6 h Propulsid, Janssen-Cilag, Issy Les Moulineaux, France) was added [15].…”
Section: Enteral Supportmentioning
confidence: 99%
“…53,54 Studies comparing individual agents with placebo have demonstrated prokinetic agents to be effective for promoting gastric emptying in critically ill patients. [22][23][24][25] In a randomized, controlled study of 21 critically ill patients, Spapen et al 22 showed that cisapride promotes gastric emptying as assessed by the volume of gastric residuals and bedside scintigraphy compared with placebo. During the 7-day study period, the mean gastric residual volume was significantly higher and gastric emptying significantly slower in the placebo group than in the cisapride group (p < .005).…”
Section: !mentioning
confidence: 99%
“…21 The results of studies comparing individual agents with placebo have demonstrated these agents to be effective in increasing gastric emptying, with minimal adverse effects. [22][23][24][25] Unfortunately, these studies were not selective for patients with proven intolerance to EN.…”
mentioning
confidence: 99%